People's diplomacy of Vietnam : soft power in the Resistance War, 1965-1972 - Mehta, Harish C. (Cambridge Scholars Publisher, 2019)
"This is the first full-length book on the concept of 'People's Diplomacy, ' promoted by the president of North Vietnam, Ho Chi Minh, at the peak of the Vietnam War from 1965-1972. It holds great appeal for historians, international relations scholars, diplomats, and the general reader interested in Vietnam. A form of informal diplomacy, people's diplomacy was carried out by ordinary Vietnamese including writers, cartoonists, workers, women, students, filmmakers, medical doctors, academics, and athletes. They created an awareness of the American bombardment of Vietnamese civilians, and made profound connections with the anti-war movements abroad."--